Structure, composition and diversity of tree species in Martelu Purba Nature Reserve, North Sumatra, Indonesia - AHMAD BAIQUNI RANGKUTI; KANSIH SRI HARTINI; ARIDA SUSILOWATI; RIDAHATI RAMBEY; MOEHAR MARAGHIY HARAHAP; HAFIZAH ARINAH; LASWI IRMAYANTI; PRIJANTO PAMOENGKAS; FITRI INDRIANI; PENIWIDIYANTI PENIWIDIYANTI; ALHARIS RUHIDI (Society for Indonesian Biodiversity, 2023)
Abstract. Rangkuti AB, Hartini KS, Susilowati A, Rambey R, Harahap MM, Arinah H, Irmayanti L, Pamoengkas P, Indriani F, Peniwidiyanti, Ruhidi A. 2023. Structure, composition and diversity of tree species in Martelu Purba Nature Reserve, North Sumatra, Indonesia. Biodiversitas 24: 78-85. Martelu Purba Nature Reserve is one of the conservation areas in North Sumatra that functions to protect biodiversity. However, there is limited information related to the vegetation community contained in the nature reserve. This study aimed to assess the diversity, structure and composition of tree species in the Martelu Purba Nature Reserve as well as to reveal the conservation status of the species in reserve. The research used the line transect method with a total of 112 observation plots representing various vegetation and environmental conditions. The results showed that there were 39 tree species belonging to 25 families, with 31, 25, 24, and 26 species at the tree, pole, sapling, and seedling stages, respectively. Shorea platyclados and Syzygium cerasiforme were species with the highest Important Value Index (IVI) at the tree and pole stages with 173.04% and 31.01%, respectively, while Gamblea malayana was the most important at the sapling and seedling stages with IVI of 66.43%, and 30.00%, respectively. The Shannon-Wiener diversity index (H') was categorized as low (1.58), the Margalef species richness index (DMg) was high at all growth stages, and the Evenness index (E) was high, indicating that all species were evenly distributed across the research plots. The distribution of tree diameter classes ranged from 20 - 40 cm for trees with the smallest diameter to 81-110 cm for trees with the largest diameter. Based on their conservation status, there were two species with conservation concerns, namely Coffea arabica (Endangered) and Lithocarpus maingayi (Vulnerable). The application of good silvicultural methods needs to be carried out in the context of conservation efforts. One example is through vegetative propagation of species with long flowering periods.